AN INVESTIGATION TOWARDS DEVELOPING A MOLECULAR APPROACH TO IMPROVE THE EFFICIENCY OF COCONUT BREEDING BY RAPD-MARKER ASSISTED SELECTION - J.M.D.T. Everard (International Coconut Community Journal, 1999)
Tall, dwarf green and San Ramon are three phenotypically distinct forms of coconut, currently used for production of hybrid seeds in Sri Lanka. Development of molecular markers for further improvement of important economic traits of these hybrids was thought important due to various constraints faced by conventional breeders. Sixty random primers (OPERON) were used for generation of RAPD profiles using DNA from 3 individuals of each form. All the sixty primers except one (OPC3) yielded RAPD-PCR products with coconut DNA. They generated a total of 326 consistently amplified bands of which 54 distinguished tall, dwarf green and San Ramon. Among RAPDs detected 16 and 8 were specific to tall and dwarf respectively, 18 distinguished dwarf and San Ramon from tall, 9 distinguished tall and San Ramon from dwarf and 3 distinguished tall and dwarf green from San Ramon. It is expected to study the segregation of these markers in F2 populations derived from tall x dwarf green and tall x San Ramon F1 palms.